Economic Growth, Renewable Energy Consumption, and Health Outcomes in Bangladesh: An Analysis Using Canonical Cointegrating Regression (CCR) - Imran, Khalid; Khanam, Fahima; Habib, Ahsan; Hossain, Md Saddam; Hasan, Mehedi; Haque, Md Obidul (South Asian Journal of Social Sciences and Humanities, 2025)
The global transition to renewable energy is critical for addressing climate change, ensuring energy security, and improving public health outcomes. However, in developing countries like Bangladesh, the adoption of renewable energy remains limited despite rapid economic growth and improvements in life expectancy. This study investigates the long-term relationships between life expectancy (LE), economic growth (PGDP), and renewable energy consumption (REC) in Bangladesh, aiming to bridge gaps in understanding the driving force for the adoption of renewable energy in a developing country context. Using the Canonical Cointegrating Regression (CCR) method, the study analyzes data from 1991 to 2022, accounting for non stationarity and long-run dependencies. The results reveal that a 1% increase in economic growth leads to a 0.169% rise in renewable energy consumption, while a 1-year increase in life expectancy results in a 5.059% increase in renewable energy adoption. These outcomes emphasize the importance of integrating economic and health policies to promote renewable energy adoption. The study concludes with actionable policy recommendations, including incentivizing renewable energy investments, enhancing public awareness, and strengthening policy frameworks to accelerate Bangladesh’s energy transition. This study provides a contribution to the growing literature on renewable energy adoption in developing countries and provides critical insights for policymakers, energy providers, and environmental organizations.